2020
DOI: 10.2147/cmar.s277927
|View full text |Cite
|
Sign up to set email alerts
|

<p>Inflammatory Marker Predicts Outcome of Oral Squamous Cell Carcinoma Receiving Chemo-Radiotherapy</p>

Abstract: Background: Inflammation is involved in the progression of oral squamous cell carcinoma. We therefore postulate that a blood-based inflammatory marker, the neutrophil-tolymphocyte ratio, could help to predict the prognosis in patients with oral squamous cell carcinoma receiving chemo-radiotherapy, and build a prognostic nomogram. Methods: In 111 cases of oral squamous cell carcinoma, several baseline variables, including inflammatory markers and lactate dehydrogenase, were measured within the week of chemoradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…When bone marrow suppression occurs, hematopoietic stem cells cannot produce adequate number of blood cells who have normal function, resulting in complications such as anemia, infection, and bleeding; these complications lower the survival of the patient severely. Several studies show that inflammation factors in the blood (for example, NLR, Journal of Oncology lymphocyte count, and neutrophil count) can predict the prognosis of patients with a variety of tumors [28][29][30][31]. Lymphocytes are related to host immunity.…”
Section: Discussionmentioning
confidence: 99%
“…When bone marrow suppression occurs, hematopoietic stem cells cannot produce adequate number of blood cells who have normal function, resulting in complications such as anemia, infection, and bleeding; these complications lower the survival of the patient severely. Several studies show that inflammation factors in the blood (for example, NLR, Journal of Oncology lymphocyte count, and neutrophil count) can predict the prognosis of patients with a variety of tumors [28][29][30][31]. Lymphocytes are related to host immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have studied OSCC patients and found that LDH levels increase due to increased exfoliation of epithelial cells. 14 Cancerous cells express growth factors and MMPs to degrade type IV collagen fibres in the basement membrane. Stromal cells at the border of OSSC express these enzymes, and elevate levels are diagnostic.…”
Section: Discussionmentioning
confidence: 99%